Landscape features influencing nesting site selection of Columba livia and Patagioenas maculosa in a South American desert city - Fernandez Maldonado, Viviana Noemi (2017)
Urban centers are dominated by species adapted to human presence. The intensityof human activity has a strong influence on habitat selection by animal populations across land-scapes. The objectives of this study were to assess the abundance and the spatial distribution ofthe nests of two species of pigeons (Columba livia and Patagioenas maculosa), and evaluate theeffects of human factors on the probability of nesting-site selection in different urban zones withina desert city. Nest abundance increased for Columba livia in city centers and for Patagioenas maculosain zones away from them, in green areas. The most important variables influencing the probabilityof nesting-site selection by Columba livia were distance to the main square, distance to food sourcesand the interaction between distance to food sources and distance to water, along with type andheight of buildings. For Patagioenas maculosa, the variables influencing the probability of nesting-site selection were distance to water, human population density, distance to food sources and theinteraction between human population density and distance to food sources, along with treeheight and diameter of tree canopy. This species selected Platanus× hispanica and Morus spp. asnesting sites. Nesting sites could be a limiting factor for these species, and our results haveimportant implications for choosing appropriate control strategies for the management of urbanpigeons in desert environments.